Optogenetic activation of serotonergic neurons enhances anxiety-like behaviour in mice. (21st May 2014) - Ohmura, Yu; Tanaka, Kenji F.; Tsunematsu, Tomomi; Yamanaka, Akihiro; Yoshioka, Mitsuhiro
Abstract: Whether increased serotonin (5-HT) release in the forebrain attenuates or enhances anxiety has been controversial for over 25 yr. Although there is considerable indirect evidence, there is no direct evidence that indicates a relationship between acute 5-HT release and anxiety. In particular, there is no known method that can reversibly, selectively, and temporally control serotonergic activity. To address this issue, we generated transgenic animals to manipulate the firing rates of central 5-HT neurons by optogenetic methods. Activation of serotonergic neurons in the median raphe nucleus was correlated to enhanced anxiety-like behaviour in mice, whereas activation of serotonergic neurons in the dorsal raphe nucleus had no effect on anxiety-like behaviour. These results indicate that an acute increase in 5-HT release from the median raphe nucleus enhances anxiety.